Efficacy of the Integrative Acupuncture and Moxibustion Treatment in Patients With Major Depressive Disorder: The Study Protocol for a Multicenter, Single-Blinded, Randomized Trial in China - Zhang, Yuan; Liu, Yamin; Ning, Baile; Yan, Luda; Wu, Lihua; Zhang, Delong; Li, Changhong; Ouyang, Wenwei; Su, Shengyong; Jiang, Shuo; Zhang, Guangcai; Xu, Junfeng; et al. (Frontiers in Medicine, 2022)
Introduction: Antidepressants are the front-line treatments for major depressive disorder (MDD), but remain unsatisfactory in outcome. An increasing number of patients are interested in acupuncture and moxibustion treatment as complementary therapies. This study aims to evaluate the efficacy and safety of integrative acupuncture and moxibustion (iAM) treatment in patients with MDD. Methods and Analysis: This multicenter, single-blind, 2 × 2 factorial randomized trial will enroll 592 patients with MDD of moderate severity from nine hospitals. All patients will be randomized, in a ratio of 2:2:2:1, through a computerized central randomization system, into four groups (the combined, iAM-only, sertraline-only, and placebo groups). Participants will undergo a 12-week intervention with either 50 mg of sertraline or a placebo once a day and active/sham iAM treatment three times per week. The primary outcome is depression severity, assessed using the Hamilton Depression Scale-17. The secondary outcomes include self-rated depression severity, anxiety, and sleep quality. The primary and secondary outcomes will be measured at weeks 0, 4, 8, 12, and the 8th week posttreatment. Safety will be evaluated through liver and kidney function tests conducted before and after treatment and through monitoring of daily adverse events. An intent-to-treat principle will be followed for the outcome analyses. Conclusion: This trial will provide sufficient evidence to ascertain whether iAM is effective and safe for treating MDD and provides a suitable combination strategy for treating MDD. Study Registration: This study was approved by the Ethics Committee of the Second Affiliated Hospital of Guangzhou Chinese Medical University (No. BF2020-186), and the trial protocol was registered at the Chinese Clinical Trials Registry (ChiCTR2100042841).